2022
DOI: 10.1126/science.abk0853
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variance in fitness indicates rapid contemporary adaptive evolution in wild animals

Abstract: The rate of adaptive evolution, the contribution of selection to genetic changes that increase mean fitness, is determined by the additive genetic variance in individual relative fitness. To date, there are few robust estimates of this parameter for natural populations, and it is therefore unclear whether adaptive evolution can play a meaningful role in short-term population dynamics. We developed and applied quantitative genetic methods to long-term datasets from 19 wild bird and mammal populations and found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
80
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 100 publications
(82 citation statements)
references
References 221 publications
2
80
0
Order By: Relevance
“…These data, in combination, are key for studying the evolution of sociality. Extensive pedigrees have been used to look at, as examples, the contribution of additive genetic effects to the gut microbiome (Grieneisen et al 2021 ) and for estimating rates of contemporary adaptive evolution in wild animal populations (Bonnet et al 2022 ). We hope that other long-term field studies join in further investigating the relative importance of genetic versus non-genetic effects in driving variation in sociality, as this information is crucial to understanding how a population can respond to selection and thus the potential for adaptive evolution in sociality.…”
Section: Discussionmentioning
confidence: 99%
“…These data, in combination, are key for studying the evolution of sociality. Extensive pedigrees have been used to look at, as examples, the contribution of additive genetic effects to the gut microbiome (Grieneisen et al 2021 ) and for estimating rates of contemporary adaptive evolution in wild animal populations (Bonnet et al 2022 ). We hope that other long-term field studies join in further investigating the relative importance of genetic versus non-genetic effects in driving variation in sociality, as this information is crucial to understanding how a population can respond to selection and thus the potential for adaptive evolution in sociality.…”
Section: Discussionmentioning
confidence: 99%
“…The field of conservation genetics has its roots in understanding the genetic and evolutionary mechanisms that negatively affect small and threatened populations, such as inbreeding, random genetic drift, and genetic load (Frankham et al, 2010). More recently, there has been greater recognition of the importance of genetic variation in facilitating adaptation and resilience to change (Hoffmann et al, 2021, Bonnet et al, 2022). We argue here that we now need to consider further how we can harness evolutionary processes (evolutionary adaptation) to enable the coexistence of native prey and invasive predators.…”
Section: Essaymentioning
confidence: 99%
“…The Tiritiri Mātangi and Kārori populations (the two populations of interest) occur at the two extremes of this range (i.e., the sanctuaries are 525 kms apart), with hihi monitored since reintroduction and lay date and reproductive success consistently recorded for both populations. Previous studies have demonstrated that both populations contain low levels of genetic diversity (Brekke et al, 2011;de Villemereuil, Rutschmann, Lee, et al, 2019), low levels of additive genetic variance and therefore a low adaptive potential (Bonnet et al, 2022;Rutschmann et al, 2020). This low ability to adapt for hihi is in contrast to other species where higher adaptive potential has enabled a shift towards earlier lay dates in response to climate change (Charmantier & Gienapp, 2014; for a New Zealand species see: Teplitsky et al, 2010).…”
mentioning
confidence: 99%